Environmental & architectural phenomenology. Vol. 17, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2006)
Vol. 17, No. 3, Fall 2006 (includes “items of interest,” “citations received,” book review of Chirstopher Alexander's Nature of Order, and essay by Silke Schilling).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals